Stillbirth in Australia 3: Addressing stillbirth inequities in Australia: Steps towards a better future. Issue 6 (November 2020) - Rumbold, Alice R.; Yelland, Jane; Stuart-Butler, Deanna; Forbes, Madeline; Due, Clemence; Boyle, Frances M.; Middleton, Philippa
Abstract: Persistent disparities in stillbirth risk and care are present in Australia. Eliminating these disparities is possible with a commitment to enhancing and scaling up models of culturally safe maternity care shown to be effective for Aboriginal and Torres Strait Islander women and those of migrant and refugee backgrounds. Campaigns to improve public awareness of stillbirth also play an important role in reducing stillbirth risk and consequences. To achieve reach and impact in communities at risk, messaging needs to be framed around the social and cultural context of women's lives. Here we describe important initiatives underway within the Stillbirth Centre of Research Excellence to develop a coordinated national approach to stillbirth prevention and care in communities that bear a disproportionate burden of stillbirth.